Development of Five-Tier Multiple Choice (5TMC) Instrument to Analyze Misconceptions in Stoichiometry Material - Idha Ayu Kusumaningrum; Maulidiningsih Maulidiningsih (Universitas Sebelas Maret, 2025)
Stoichiometry is the basic of chemical calculations. However, students' understanding of the material is still poor. The characteristics of the material consist of abstract concepts, calculations, and related with other materials. That can cause misconception. The instrument to analyze misconceptions and the cause of student’s misconceptions is still rare. This study aims to determine the feasibility of the five-tier multiple choice (5TMC) instrument and analyze misconceptions and the causes of misconceptions. The instrument was developed using the 4-D model (Define, Design, Develop, and Dissemination). This research was conducted with 103 respondents. Data was obtained from questionnaires, interviews, and tests. Content validity used the Aiken method with 5 experts. This research also used the Rasch Model to analyze the reliability and validity of the instrument. The research concluded that the five-tier multiple choice (5TMC) instrument developed was feasible and the criteria were good based on Aiken validity, Rasch model, and response questionnaire. Misconception was found in 2nd students as moderate (38,09%) and 4th students as low (24,94%). Personal thinking is the factor that most influences misconceptions. This instrument can be used as an alternative for analyzing student’s misconceptions so that lecturers can take remediation